WRITING ANXIETY IN AN AFGHAN EFL SETTING: VOICES FROM FIVE AFGHAN STUDENTS - Miri, Mir Abdullah; Joia, Jamhor (Journal of Foreign Language Teaching and Learning, 2018)
Language writing anxiety is a phenomenon that majority of EFL students, particularly Afghan English language learners, experience. To address this issue, this qualitative study explored the reported experiences of five Afghan undergraduate English majors, studying at an Afghan university, with writing anxiety. After collecting data through semi-structured interviews, the data was transcribed verbatim, and four major themes were constructed. The results revealed that anxiety has both positive and negative effects on students. The findings also showed that participants? little exposure to writing activities was the major reason behind their writing anxiety. The participants reported that receiving feedback from teachers, doing extensive reading, developing their vocabulary knowledge and practicing writing were the major strategies they had used to overcome writing anxiety.